Road to language competence in the mother tongue education of children aged 6- 10: the central role of syntagms in the NYIK-program of József Zsolnai (Training and Practice : Journal of Educational Sciences, 2021)
The NYIK educational program of József Zsolnai has been included as an alternative curriculum since 1984. We analyzed video recordings of the NYIK-program’s elementary school lessons from the 1980s-90s. Our finding is that syntagms have been the focus of this teaching program. This fact is unusual in the mother tongue education of 6-10 year old students even today. But the (nativist) theses of linguistics - the acquisition of linguistic competence - justify the importance of early awareness of syntagmatic relationships.